Vivir en público y paideía privada en las Cartas a Lucilio de L.A. Séneca - Mingo, Alicia de (2011)
“Living in Public and Private Paideía in Seneca’s Epistulae morales adLucilium”. It is difficult to conceive both moral life and communitarian life withoutthe tension between the Others and the self. On the one hand, due to the cohesionof society and the individual’s search for its communitarian dimension, a sort oftransparent life, without secrets, as long as it is honest, is needed. However, onthe other hand, when the social surrounding is morally reproachable, a privatepaideía, which allows the moral orientation of the individual, is indispensable,even if this produces in him solitude and brings the incomprehension from hisfellow citizens, resulting in the construction of a private space.